2018
DOI: 10.1111/obr.12678
|View full text |Cite
|
Sign up to set email alerts
|

The impact of junk food marketing regulations on food sales: an ecological study

Abstract: Utilizing a novel approach to evaluate junk food broadcast marketing policies, the study demonstrated that countries with statutory policies saw a significant decrease in junk food sales per capita not seen in countries with no or only self-regulatory policies. To effectively reduce exposure to child-targeted junk food marketing, governments should establish strong, comprehensive statutory regulations. Additionally, countries that implement junk food marketing policies can use food sales data to track policy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 26 publications
1
45
0
1
Order By: Relevance
“…However, scientific evidence showed that regulatory approaches seemed more effective in reducing the number of unhealthy food advertising and on marketing exposure when compared to self-regulation initiatives [81, 82]. A more recent study also showed that countries with regulatory approaches observed a significant decrease in junk food sales per capita than in countries with no or only self-regulatory policies [83]. Promoting changes in food provision in public settings may also have an effect on food choices and diet-related NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, scientific evidence showed that regulatory approaches seemed more effective in reducing the number of unhealthy food advertising and on marketing exposure when compared to self-regulation initiatives [81, 82]. A more recent study also showed that countries with regulatory approaches observed a significant decrease in junk food sales per capita than in countries with no or only self-regulatory policies [83]. Promoting changes in food provision in public settings may also have an effect on food choices and diet-related NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, policy responses to limit the impact of unhealthy food marketing on children should seek to limit children’s exposures to unhealthy food marketing and the persuasive power of such promotions. Globally, a number of countries have implemented regulatory responses to limit children’s exposure to, and the power of, unhealthy food marketing [37]; demonstrating that regulatory approaches are possible and can be effective in reducing food marketing exposure, power and impact (e.g., [38]).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommends restricting television advertising to children for products high in saturated fat, trans fatty acids, free sugar, or salt [27]. While many countries have taken action to limit less-healthy food advertising to children, no country to our knowledge has yet implemented a 9:00 PM watershed [28,29]. A cross-country comparison found that those countries that had statutory regulations experienced a smaller increase in household expenditure on less-healthy food and drink products over time [28].…”
Section: Introductionmentioning
confidence: 99%
“…While many countries have taken action to limit less-healthy food advertising to children, no country to our knowledge has yet implemented a 9:00 PM watershed [28,29]. A cross-country comparison found that those countries that had statutory regulations experienced a smaller increase in household expenditure on less-healthy food and drink products over time [28]. A recent study estimated that a 9:30 PM watershed in Australia would reduce mean BMI by 0.35 kg/m 2 amongst children, be cost saving, and reduce inequalities in childhood obesity.…”
Section: Introductionmentioning
confidence: 99%